G64(P) What evidence is available to support the development of a regional specialist neuro-rehabilitation outreach service. (May 2019) - Bhowaneedin, A; Smith, H; Deeley, H; Reyes Payeras, C; Keating, O; Smallbone, T; Wright, I; Sharples, PM
Abstract : Background: The WHO recognises several specialist rehabilitation provision models; in-patient, outpatient and outreach. Intensive early neurorehabilitation is required after severe Acquired Brain Injury (ABI), usually necessitating in-patient care. In the UK, children receiving specialist neurorehabilitation often remain in-patients for long periods because of the lack of appropriate out-of-hospital provision. Aims: To explore feasibility and funding implications of developing a regional specialist neurorehabilitation outreach service to facilitate earlier discharge. Methods: Analysis of data on children receiving in-patient neurorehabilitation at a paediatric Regional Neuroscience Centre (RNSC), 2014–2018. Information concerning therapy provision was obtained from Trust Clinical Information System Suite (CISS). Patient dependency and rehabilitation complexity was assessed by Rehabilitation Complexity Scale--Extended (RCS-E), scored by multi-disciplinary team (MDT) at weekly meetings over 15 months. For modelling purposes, a specialist neurorehabilitation outreach tariff equating to 50% in-patient tariff was assumed. Data analysis was undertaken by linear programming model ( XpressIve©) and Discrete-Even Simulation (Simul8©). Various eligibility criteria for outreach provision were modelled: 1) needing > 1 therapies<3 times/week; 2) Total RCS-E score <9, <11 or<13; 3) Therapy Dependency (TD) +Therapy Intensity (TI) components of RCS-E < 5. Results: 156 children received neurorehabilitation as in-patients over 4 years. Mean age=7.34 years (range 0.1–17). 66 (55%) were male, 53 (45%) female. 84% had ABI, others acquired spinal injury, acute polyneuropathy or somatisation disorders. 52% lived >40 miles from RNSC, 47%>60 min' drive away. 49% were inpatients 1–28 days; 34%, 29–84 days; 18, 85–168 days; 6, >168 days. Patients showed significant functional improvements between admission to neurorehabilitation and discharge (p<0.001). Modelling suggests 14 outreach centres, including RNSC, would be required to permit 78% patients to access specialist neurorehabilitation <30 mins drive from home; 10 centres would permit 92% to access neurorehabilitation <45 min' drive away; 8 centres would permit 96% to access neurorehabilitation <60 min' drive away. Calculations assuming outreach tariff=50% in-patient tariff, and various RCS data models, suggest annual cost savings ranging from £53, 424-£166, 950; calculations based on CISS data, suggest average savings of £1 05 596 per year (range £98, 500-£113, 526). Conclusion: Modelling supports the feasibility and affordability of specialist neurorehabilitation outreach provision, although efficacy remains uncertain.